Sex differences and adherence of patients treated with wearable cardioverter-defibrillator: insights from an international multicenter register - Abumayyaleh, Mohammad S. A.; Dreher, Tobias C.; Rosenkaimer, Stephanie L.; Röger, Susanne; Erath, Julia W.; Klein, Norbert; Kovacs, Boldizsar; Duru, Firat; Saguner, Ardan M.; El-Battrawy, Ibrahim; Akın, Ibrahim (Journal of cardiovascular electrophysiology, 2022)
Aims: Treatment with the wearable cardioverter defibrillator (WCD) may protect against sudden cardiac death (SCD) as a bridging therapy until a cardioverter-defibrillator may be implanted. We analyzed in a multicenter setting a consecutive patient cohort wearing WCD to explore sex differences. Methods and Results: We analyzed 708 consecutive patients, 579 (81.8%) from whom were males and 129 (18.2%) females (age, 60.5 ± 14 vs. 61.6 ± 17 years old; p = .44). While the rate of ischemic cardiomyopathy (ICM) as a cause of prescription of WCD was significantly higher in males as compared to females (42.7% vs. 26.4%; p = .001), females received it more frequently due to nonischemic cardiomyopathy (NICM) (55.8% vs. 42.7%); p = .009). The wear time of WCD was equivalent in both groups (21.1 ± 4.3 h/days in males vs. 21.5 ± 4.4 h/days in females; p = .27; and 62.6 ± 44.3 days in males vs. 56.5 ± 39 days in females; p = .15). Mortality was comparable in both groups at 2-year-follow-up (6.8% in males vs. 9.7% in females; p = .55). Appropriate WCD shocks and the incidence of ICD implantations were similar in both groups (2.4% in males vs. 3.9% in females; p = .07) (35.1% in males vs. 31.8% in females; p = .37), respectively. In age tertile analysis, compliance was observed more in 73-91 years old group as compared with 14-51 years old group (87.8% vs. 68.3%; p < .001). Conclusion: Compliance for wearing WCD was excellent regardless of sex. Furthermore, mortality and the incidence of ICD implantations were comparable in both sexes. Appropriate WCD shocks were similar in both sexes.